The effect of digital literacy to internet addiction - Raymond Frans Deonisius; Ika Lestari; Sarkadi Sarkadi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2019)
The purpose of this study was to investigate the effect of digital literacy to internet addiction. For this purposed, we conducted a survey from 347 participants of middle school students at Menteng sub-district, Central Jakarta. This study was used a simple regression equation model to evaluate the structural model. The result showed that digital literacy positively significant affected internet addiction. Digital literacy simultaneously had a positive significant effect to internet addiction.